Lessons from Innovative Institutions in the Marketing of Fish and Fishery Products in India - B. Ganesh Kumar; T. Ravisankar; R. Suresh; Ramachandra Bhatta; D. Deboral Vimala; M. Kumaran; P. Mahalakshmi and T. Sivasakthi Devi (Agricultural Economics Research Review, 2010)
This study has been conducted with the objective of understanding the process of innovative marketing models in the fisheries sector and to draw lessons from the success stories to upscale and replicate in a similar socio-politico-economic scenario in other parts of the country. It has been conducted to provide a better understanding of fish marketing by self-help groups (SHGs), producer associations, fisheries development corporations, fisherman cooperatives and private institutions in the southern states of India, namely Tamil Nadu, Kerala, Karnataka and Andhra Pradesh with the hypothesis that the institutional arrangements in the marketing of fish and fishery products reduce the transaction cost and improve the market access and its efficiency. The study has reported the primary activities of those institutions in the efficient fish marketing, such as inbound logistics, operations, outbound logistics, marketing and sales promotion and support activities like infrastructural facilities, technological backstopping, price information and procurement. Through these advantages, the fishermen have been found to achieve economies of scale, technological innovations, capacity development, linkage among activities, degree of vertical integration, timing of market entry, product differentiation, market access, credit access, etc. The study has suggested replication of such successful innovative institutions in marketing the fish and fishery products through appropriate policies and programmes. It has also suggested to promote institutions like SHGs, producer / fishermen associations, cooperatives, etc. and allow the entry of private agencies with appropriate regulatory mechanism to improve the efficiency of fish marketing in the country.